GHOSTING SALAH SATU FENOMENA YANG TERJADI PADA APLIKASI KENCAN ONLINE BUMBLE - santi, desiana; Purwanti, Angel (SCIENTIA JOURNAL, 2022)
Ghosting is a modern adaptation of avoidance and withdrawal behavior most often implemented through technology, disconnection between partners for the purpose of breaking ties. Along with the development of the technology era and online dating applications, the term ghosting is increasingly used until it is finally recognized by many people. With increasingly sophisticated technological developments, this has brought very significant changes to changes in patterns of social interaction. ghosting on the Bumble online dating app, user characteristics and forms of communication that occur on the Bumble online dating app. This type of research is a qualitative research with an exploratory approach. Data collection techniques were carried out by observation, interviews, documentation and literature study. Researchers used the triangulation method by examining the data that had been obtained. The results of this study show who uses the Bumble application and the reasons for using the Bumble application. The behavior of someone who does ghosting is no longer responding to chats or blocking social networks. the approach taken by users of the Bumble app. Face it when you already know deeper. Then ghosting is done by informants while still chatting or even having met. The form of communication that occurs is direct communication and indirect communication. dating is not only done in person but also using an application and applications are part of new media. Keywords: ghosting, phenomenon, new media, Bumble, dating application.